(Production Technology Of Biodiesel From Jatropha Oil(Jatropha curcas L.) - Rizal Alamsyah (Balai Besar Industri Agro, 2006)
It is so far the world haevily depends on the petroleum oils to fulfill energy consumption such or automotives,industry,generators,heating, agricultural machineries and other energy needs.It was predicted that the world oils reserves will be exhausted in the next 17 years because of its nonrenewable characteristic.Many alternative energy resources have been employed to overcome energy crisis by a lot of countries in the world including Indonesia.Many eeforts have been made to anticipate the scarcity of petroleum oil.Recently,Indonesia and many other countries has develop biodisel which and chemically defined as a methyl ester derived from renewable resources such jatropha oil,palm oil,used frying oil,and other resources.Biodisel sometime addresed to also as FAME (Fatty Acids Methyl Ester)or VOME (Vegetable Oil Methyl Ester) to reccal its chemical origin.Comparing with petroleum diesel the use of bio-diesel has some benefits such as clean burning,renewable,nontoxic and biodegradable fuel.Bio-diesel can be used alone or in blends with petroleum-derived diesel.Basically bio-diesel is made through trans-esterification process with methanol.In lands availabity and technology point of view of bio diesel can produced for both industrial and rural area scale.Petroleum diesel consumption in Indonesia at the time being in around 150.000 MB.Unit now the deficid is fulfilled by import.Currently more than 1 millionton of vegetable oil methyl ester are being produced and used in the world as alternative fuel for engines and for heating.